Kemahiran berfikir kritis dalam buku teks Bahasa Melayu kurikulum standard sekolah rendah tahap dua / Nurul Hasna Hasan - Nurul Hasna , Hasan (2020)
Critical thinking is one of the most important aspects that students need to master as well as creative thinking, communication skills and collaborative learning in the 21st century learning environment. The aim of this study is to analyse critical thinking skills towards instruction in the activity and assessment of reading skills. The Directed Content Analysis method was used to test the sample of the study. The sample of the study consists of three Malay textbooks Year 4, 5 and 6 in the Primary School. Three experts were selected to verify the 'Code of Analysis in Critical Thinking Skills' instrument that has been developed. The experts consist of Malay curriculum specialists, content analysis specialists and Malay teacher‟s specialist. Instruments that have been modified by these experts are then tested by the reliability of two Malay language teachers before being used in the actual study. Analysis of the main categories in the three textbooks indicates that activity and assessment of reading skills are leads towards Collecting and Using Information Skills which are 49.1% and 64.3% respectively. The Inferential Instruction Skill ranked second the highest; activity is 46.8% and assessment is 32.1%. On the other hand, the Decision-Making Skills show less percentage; activity is 4.1% and assessment is 3.6%. However, there are no instruction in the activities and assessments that led to the Analogy Skill. Therefore, the implication of the study when the Analogy Skill is not exposed to the student is the students will be less able to use their knowledge and to think critically in beyond the classroom. Overall, this study can be benefit of the Text Books Division, KPM, publishers and authors, and teachers.